2015
DOI: 10.3402/tellusb.v67.24638
|View full text |Cite
|
Sign up to set email alerts
|

Observed changes in ocean acidity and carbon dioxide exchange in the coastal Bay of Bengal – a link to air pollution

Abstract: A B S T R A C T Variations in surface water hydrographic properties and dissolved inorganic carbon (DIC) were evaluated in the coastal Bay of Bengal using observations carried out during MarchÁApril 1991 and 2011, including 8 yr monthly time-series observations during 2005 and 2013. The coastal Bay of Bengal is characterised by relatively fresher, more basic and lower pCO 2 in 1991 compared to 2011. The rates of decrease in pH, increase in DIC and pCO 2 per decade were consistent with global trends in the sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 41 publications
1
29
1
Order By: Relevance
“…Unlike our results the pattern of north-south decline in pH value was observed in western Bay of Bengal coast (Sarma et al, 2015). It seems that the heterogeneity of pH parameter of the coast of Hadhramout not much different from South east coast of India, where slightly alkaline range in pH was reported 7.7-8.3 (Satpathy et al 2009).…”
Section: Phcontrasting
confidence: 55%
“…Unlike our results the pattern of north-south decline in pH value was observed in western Bay of Bengal coast (Sarma et al, 2015). It seems that the heterogeneity of pH parameter of the coast of Hadhramout not much different from South east coast of India, where slightly alkaline range in pH was reported 7.7-8.3 (Satpathy et al 2009).…”
Section: Phcontrasting
confidence: 55%
“…The input of such acidic waters to the coastal BoB may have significant impact on the inorganic carbon system. Recently, Sarma et al (2015) reported coastal water acidification due to increased anthropogenic aerosol loading in the northern BoB in winter and spring during recent decades, and the pH of the coastal waters decreased at the rate of 0.007 units yr À 1 , which was 2-3 times higher than that of elsewhere in the world. Sarma et al (2012b) reported that the direction of CO 2 flux (source or sink) from the coastal western BoB was dependant on the characteristics of the discharged water from the rivers.…”
Section: Introductionmentioning
confidence: 95%
“…There has been no routine monitoring of surface ocean pCO 2 of the Bay of Bengal except for a few research‐based cruises focusing on the coastal areas of the Bay (Sarma et al, , ). A data‐based assessment of carbon cycle of the upper ocean Bay of Bengal is thus not feasible and that forces studies to resort on biogeochemical models (Sarma et al, ).…”
Section: Introductionmentioning
confidence: 99%